The Black studies reader - Bobo, Jacqueline; Hudley, Cynthia; Michel, Claudine (Routledge, 2004)
Black studies emerged from the tumultuous social and civil rights movements of the 1960s and empowered African Americans to look at themselves in new ways and pass on a dignified version of Black history. However, it also enriched traditional disciplines in profound and significant ways. Proponents of Black and ethnic studies confronted the false notion that scholarly investigations were objective and unbiased explorations of the range of human knowledge, history, creativity, artistry, and scientific discovery. As they protested against hegemonic notions like universal psychology and re-evaluated canonical texts in literature, a new model of academic inquiry evolved: one committed to serving a range of populations, that critiqued traditional politics, culture, and social affairs, and worked with activist energy for the transformation of the existing social order. With an all-star cast of contributors, The Black Studies Reader takes on the history and future of this multi-faceted academic field. Topics include Black feminism, cultural politics, Black activism, lesbian and gay issues, African American literature and film, education, and religion. This authoritative collection takes a critical look at the current state of Black studies and speculates on where it may go from here.
Keywords: LGBTQIA2+; afro-féminisme; amériques; approches et analyses; féminisme islamique; histoire et politique; identités LGBTQIA2+; militance; outils; ouvrages de références; racisme; ressource en ligne; régions géographiques; sexualité; système colonial; systèmes d'oppressions; thématiques; états-unis

Militantisme et recherche féministe au Québec - Descarries, Francine (Labrys (en ligne), 2004)
Keywords: SAC; amériques; approches et analyses; histoire et politique; incomplet; militance; québec; rapports sociaux de sexe; recherche partenariale; ressource en ligne; régions géographiques; thématiques

Stolen From Our Bodies: First Nations Two-Spirits/Queers and the Journey to a Sovereign Erotic - Driskill, Qwo-Li (Studies in American Indian Literatures, 2004)
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amériques; approches et analyses; autothéorie; cherokee; cours; discipline; féminisme autochtone; militance; premier cycle; premières nations; périodes historiques; queer; régions géographiques; sexualité; soc2014; système colonial; systèmes d'oppressions; thématiques; états-unis

Les femmes dans les associations du secteur environnement - Flahault, Erika (Femmes et villes, 2004)
Keywords: 2000 à aujourd'hui; 2000-2009; environnement; europe; france; militance; projet charge mentale; périodes historiques; ressource en ligne; régions géographiques; thématiques; travail

Recherche-Action : notes de réflexion sur leur articulation - Galerand, Elsa (Labrys, 2004)
La question qui m’a été adressée -comment se manifeste ton engagement féministe dans tes recherches et dans tes actions? -, m’interpelle sur trois fronts puisque je suis féministe, que je milite depuis plusieurs années et que je fais partie de la classe privilégiée des universitaires. Étudiante au doctorat en sociologie, je travaille actuellement sur la Marche mondiale des femmes en tant que processus de mobilisation collective sexué (D. Kergoat, 1992). Processus dont je suis partie prenante et au sein duquel j’ai eu l’occasion d’effectuer une immersion particulière au cours de l’année 2000, en participant à titre d’étudiante – stagiaire à l’équipe d’organisation et de coordination au niveau international. Et à toutes ces choses, correspond un même préalable dans mon parcours : l’expérience de l’oppression patriarcale.
Keywords: approches et analyses; discipline; incomplet; militance; outils; point de vue situé; recherche en milieux de pratique; recherche partenariale; recherche-action; ressource en ligne; sciences humaines; sociologie; sofia; thématiques

Dictionnaire critique du féminisme - Hirata, Helena (Presses universitaires de France, 2004)
Avortement et contraception, citoyenneté, division sexuelle du travail et rapports sociaux de sexe, domination, famille, féminité-masculinité-virilité, harcèlement sexuel, histoire (sexuation de l'), maternité, migration, mixité, mondialisation, mouvements féministes, parité , patriarcat (théories du), précarisation sociale, prostitution, sexualité, transmissions intergénérationnelles, syndicats, travail domestique, violences.dictionnaire est de changer la façon commune de penser " : l'ambition de Diderot est reprise avec force par les auteurs de ce parcours historique etcritique duféminisme . Cette volonté éditoriale s'exprime dans le choix typologique des entrées : des concepts nouveaux issus de la théorisation féministe, des champs d'intervention des luttes féministes, des notions transversales d'économie et de sociologie du travail.Dictionnaire théorique et politique, pluriel et engagé, cet ouvrage se veut aussi un texte de conviction et d'explication.
Keywords: 1900-1999; approches et analyses; avortement; corps; cours; cycles supérieurs; dictionnaire critique; discipline; europe; fem1000; fem7000; france; har4600; histoire et politique; interdisciplinarité; justice reproductive; lit2815; lit3220; lit3495; militance; outils; ouvrages de références; philosophie; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; santé; sciences humaines; sexualité; sociologie; thématiques; travail

Feeling beyond rules: Politicising the sociology of emotion and anger in feminist politics - Holmes, Mary (European Journal of Social Theory, 2004)
The part anger plays in motivating political action is frequently noted, but less is said about ways in which anger continues to be a part of how people do politics. This article critically assesses approaches to emotions that emphasize managing anger in accordance with ‘feeling rules’. It reflects on the utility of Marxist notions of conflict as the engine of change for the understanding of how anger operates in political life. This involves understanding the ambivalence of anger and its operation within particular power relations. Shifting sets of conventions have had some continuity in discouraging women in Western nations (particularly white and middle-class women) from showing anger. But clearly, women do get angry and feminists have drawn on anger in acting politically. New Zealand feminist writings from the ‘second wave’ are taken as illustrative of the common difficulties Western feminists faced in dealing with anger. These difficulties were due to trying to juggle social conventions about femininity, the political ideal of sisterhood, and the realities of dealing with other women in often new and experimental political processes. Anger could be personalized and hurtful, but in certain cases its expression was constructive in producing more respectful relations. Exploring these cases makes it clear how anger produces, and is produced by, relations with others.
Keywords: 1900-1999; 1970-1979; 1980-1989; colère; discipline; débat; militance; mouvements féministes; nouvelle-zélande; océanie; périodes historiques; rapports de pouvoir; ressource en ligne; régions géographiques; sciences humaines; sociologie; thématiques; émotions

Femmes et pouvoirs : à la conquête des territoires - Institut de recherches et d'études féministes (FéminÉtudes, 2004)
Cette publication aborde les conquêtes passées et en cours pour l’accès au pouvoir des femmes. *** FéminÉtudes est une revue étudiante, féministe et multidisciplinaire. La revue est née en 1995 de l’initiative d’étudiantes féministes dans l’intérêt de partager leurs recherches et de créer un groupe affinitaire. La revue est dirigée par des collectifs de rédaction bénévoles et autogérés, et soutenue par l’Institut de Recherches en Études Féministes (IREF) de l’Université du Québec à Montréal. Au fil des ans, FéminÉtudes a réussi à se bâtir une réputation et une légitimité dans le champ de la recherche en études féministes, tout en offrant une tribune au travaux et aux réflexions de dizaines d’étudiant.e.s. Au-delà de la recherche, c’est également pour l’avancement des luttes féministes que FéminÉtudes souhaite continuer à grandir.
Disponible en libre accès : https://iref.uqam.ca/feminetudes/vol-9-no-1-2004-femmes-et-pouvoirs/
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; corps; droits des femmes*; espace public; féminétudes; histoire et politique; militance; pouvoir; périodes historiques; québec; ressource en ligne; régions géographiques; thématiques

Militer - Lévesque, Andrée (Le siècle des féminismes, 2004)
Keywords: 1900-1999; cours; fem1000; militance; mouvements féministes; premier cycle; périodes historiques; thématiques

Pornography embodied: from speech to sexual practice - Mason-Grant, Joan (Rowman & Littlefield, 2004)
What does it mean to conceptualize pornography as a material practice rather than as speech? Mason-Grant argues that this idea, fundamental to the work of Andrea Dworkin and Catharine MacKinnon, has been obscured in legal wrangling and political polarization over their civil ordinance. Within the arena of legal argument, where the principle of free speech holds sway for progressive thinkers, their analysis of pornography is rendered, at worse, an apology for censorship and, at best, an argument about the social force of speech, rather than recognized as a fundamental challenge to the very idea of pornography as speech. In this book, Mason-Grant first shows how the persistent 'speech paradigm' inevitably obscures the innovative core of the Dworkin-MacKinnon critique of mainstream pornography. She then develops an alternative 'practice paradigm' that critically engages their analysis, capturing and extending its core insights about the role of pornography in sexual practice. Drawing on phenomenology of the lived body, this alternative paradigm provides a way of re-thinking how the pervasive use of mass-market heterosexual pornography contributes to the cultivation of an embodied and tacit sexual know-how that is subordinating, and raises important questions about alternative materials produced and used by sexual minorities. In her conclusion, Mason-Grant considers the implications of her analysis not for law, but for a critical pedagogy in youth sexuality education.
Section: x, 193 pages
Keywords: approches et analyses; corps; cours; discipline; discours dominant; féminisme pop; hétérosexisme; militance; patriarcat; philosophie; phénoménologie; premier cycle; pédagogie; sciences humaines; sex1911; sexisme; sexualité; sofia; systèmes d'oppressions; thématiques

Namaji: Two-Spirit Organizing in Montreal, Canada - Meyer-Cook, Fiona; Labelle, Diane (Journal of Gay & Lesbian Social Services, 2004)
This article traces the authors' involvement in Two-Spirit organizing in Montreal since 1995. The term Two-Spirit is often used by lesbian, gay, bisexual and transgendered (LGBT) people of Aboriginal descent in both the U.S. and Canada. The authors explore the multifaceted aspects of organizing within a Two-Spirit community. They begin with an examination of contemporary challenges facing Two- Spirit people within Canadian society and then provide several concrete examples of local organizing, ranging from the creation of an educational video on HIV/AIDS and participation in a collaborative project with a school of social work to national and international alliance-building.
Publisher: Taylor & Francis
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amériques; approches et analyses; canada; cours; discipline; féminisme autochtone; histoire et politique; militance; montréal; personnes bispirituelles; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; soc2014; thématiques; travail social; études gaies et lesbiennes

Des modèles nationaux (1940-1945)? - Offen, Karen (Le sièce des féminismes, 2004)
Extrait de la couverture : "Le féminisme apparaît aujourd'hui comme un événement majeur, facteur d'une révolution sociale et culturelle sans précédent du XXe siècle. Pour la première fois dans l'histoire de l'Occident, les femmes se sont émancipées de la tutelle familiale et de leur incapacité juridique, ont acquis une indépendance économique, intellectuelle et sexuelle, et se sont imposées sur la scène publique et politique. Et pourtant, en ce début du XXIe siècle, le mouvement de libération des femmes semble à un tournant. En effet, il a pris une ampleur mondiale, fait partie intégrante des grands débats de société et resurgit là où on l'attendait le moins, notamment parmi les jeunes femmes de banlieue. ... Synthèse unique d'un siècle de combats des femmes, cet ouvrage n'a pas pour but d'entrer dans la polémique mais de l'éclairer par la précision du regard historique. Il offre au public le fruit de recherches internationales encore méconnues qui, depuis trente ans, ont défriché un nouveau champ de savoir. La pluralité des combats féministes y est retracée sans complaisance : de la lutte pour le droit de vote aux combats pour la dépénalisation de l'avortement et la libération sexuelle, en passant par le droit à l'éducation et au travail."
Keywords: 1900-1999; 1940-1949; changement social; cours; discipline; droits des femmes*; fem1000; histoire; histoire des femmes*; histoire et politique; militance; premier cycle; périodes historiques; sciences humaines; thématiques

Le siècle des féminismes - Gubin, Eliane; Studer, Brigitte; Jacques, Catherine; Rochefort, Florence; Thébaud, Françoise; Zancarini-Fournel, Michelle (L'Atelier, 2004)
Le féminisme apparaît aujourd'hui comme un événement majeur, facteur d'une révolution sociale et culturelle sans précédent du XXe siècle. Pour la première fois dans l'histoire de l'Occident, les femmes se sont émancipées de la tutelle familiale et de leur incapacité juridique, ont acquis une indépendance économique, intellectuelle et sexuelle, et se sont imposées sur la scène publique et politique. Et pourtant, en ce début du XXIe siècle, le mouvement de libération des femmes semble à un tournant. En effet, il a pris une ampleur mondiale, fait partie intégrante des grands débats de société et resurgit là où on l'attendait le moins, notamment parmi les jeunes femmes de banlieue. ... Synthèse unique d'un siècle de combats des femmes, cet ouvrage n'a pas pour but d'entrer dans la polémique mais de l'éclairer par la précision du regard historique. Il offre au public le fruit de recherches internationales encore méconnues qui, depuis trente ans, ont défriché un nouveau champ de savoir. La pluralité des combats féministes y est retracée sans complaisance : de la lutte pour le droit de vote aux combats pour la dépénalisation de l'avortement et la libération sexuelle, en passant par le droit à l'éducation et au travail.
Keywords: 1900-1999; changement social; cours; discipline; fem1000; har4600; histoire; militance; mouvements féministes; occident; premier cycle; périodes historiques; sciences humaines; thématiques

Organizational "emotion work" through consciousness-raising: An analysis of a feminist organization - Reger, Jo (Qualitative Sociology, 2004)
In this article I explore how organizational processes link to certain emotional responses, as a way of investigating more fully the role emotions play in social movements. Through the construction of a case study of a feminist group, the New York City chapter of the National Organization for Women (NYC NOW), I analyze how certain emotions, such as anger, alienation, hopelessness and frustration, are redefined within an organizational context. I find that consciousness-raising serves as the organizational process that helps transform personal emotions into a collectively defined sense of injustice. This transformation has the potential of creating actors dedicated to chapter activism.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; care; discipline; militance; mouvements féministes; new york; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sociologie; thématiques; émotions; états-unis; étude qualitative

Creating emotional resonance: Interpersonal emotion work and motivational framing in a transgender community - Schrock, Douglas; Holden, Daphne; Reid, Lori (Social Problems, 2004)
In this article, we examine how interpersonal emotion work in a transgender support group and motivational framing of transgender social movement organizations together constructed favorable conditions for emotional resonance. We define emotional resonance as the emotional harmony and/or disjuncture between collective action frames and the emotional lives of potential recruits. Data derive from fieldwork, interviews, online e-mail lists and forums, community publications, activist speeches, and social movement organizations' recruitment appeals. Transgendered people joined support groups hoping to find relief from shame, fear, powerlessness, alienation, and inauthenticity. Although group members' emotion work partly accomplished such relief, it was hindered by identity conflicts and the temporal bounds of the meetings. Transgender activists and nascent social movement organizations, however, used motivational framing to promise targeted recruits a more permanent emotional resolution—one which could draw them into the movement. Our analysis moves transgender scholarship beyond issues of identity and moves framing theory beyond an almost exclusive concern with cognitive processes.
Keywords: 1900-1999; 1990-1999; LGBTQIA2+; amériques; care; identités LGBTQIA2+; militance; mouvements sociaux; personnes trans*; périodes historiques; ressource en ligne; régions géographiques; thématiques; émotions; états-unis